Principle-centered leadership - Covey, Stephen R. (New York : Simon and Schuster, 1991)
This book is divided into two parts: Personal and Interpersonal Effectiveness; and managerial and Organizational Development.
Keywords: Psychology; Leadership; Success in business; Leadership; Success -- Psychological aspects